Analysis of Mammalian Native Elongating Transcript sequencing (mNET-seq) high-throughput data - Prudêncio, Pedro (2020)
Mammalian Native Elongating Transcript sequencing (mNET-seq) is a recently developed technique that generates genome-wide profiles of nascent transcripts associated with RNA polymerase II (Pol II) elongation complexes. The ternary transcription complexes formed by Pol II, DNA template and nascent RNA are first isolated, without crosslinking, by immunoprecipitation with antibodies that specifically recognize the different phosphorylation states of the polymerase large subunit C-terminal domain (CTD). The coordinate of the 3' end of the RNA in the complexes is then identified by high-throughput sequencing. The main advantage of mNET-seq is that it provides global, bidirectional maps of Pol II CTD phosphorylation-specific nascent transcripts and coupled RNA processing at single nucleotide resolution. Here we describe the general pipeline to prepare and analyse high-throughput data from mNET-seq experiments.